THE AGENDA OF THE DEVELOPED WORLD (IN WANDERING SEARCH OF THE BEST WAYS OF TECHNOLOGICAL BREAKTHROUGH) - SERGEY ALEKSEEVICH Pobyvayev (Мир новой экономики)
In this article the author examines the phenomenon referred to in the current scientific and expert literature as the fourth industrial revolution or the industry 4.0. Since this issue has become a major subject of discussion at the World Economic Forum in Davos in 2016, the author analyzes the position of its chief ideologist Klaus Schwab, set out in his works and speech at the forum. We consider the threat of rising inequality due to the onset of a new technological era, which should substantially change the existence of the mankind. It is concluded that such a threat is not of any importance. Result analysis of the leading analytical companies’ research of the core of impending technological revolution - that is, data processing and telecommunications industry - led to the conclusion that the expectations of the Davos Forum in relation to the rate of conversionare redundant. At the same time one cannot deny the existence of a certain scientific and technological reserve,enough for large-scale transformations of the technological space in the developed world.